Giant photonic spin Hall effect induced by hyperbolic shear polaritons. Issue 16 (13th April 2023) - Jia, Guangyi; Xue, Wenxuan; Jia, Zhenxin; Schubert, Mathias
Abstract : A schematic illustration of the monoclinic β-Ga2 O3 crystal structure and its application in enhancing the photonic spin Hall effect. Abstract : Recently, broken symmetry within crystals has been attracting tremendous research interest since it can be utilized to effectively manipulate the propagation of photons. In particular, low-symmetry Bravais crystals can support hyperbolic shear polaritons (HShPs), holding great promise for technological upgrading in the emerging research area of spinoptics. Herein, an Otto-type multilayer structure consisting of a KRS5 prism, a sensing medium, and monoclinic β-Ga2 O3 crystals is designed to ameliorate the photonic spin Hall effect (PSHE). The surface of β-Ga2 O3 is the monoclinic (010) plane ( x – y plane). We show that giant spin Hall shifts with three (or two) orders of magnitude of the incident wavelength can be obtained in the in-plane (or transverse) directions. The azimuthal dispersions of photonic spin Hall shifts present non-mirror-symmetric patterns upon tuning the rotation angle of β-Ga2 O3 around the z -axis in the plane. All of these exotic optical properties are closely correlated with the broken crystal lattice symmetry and the incurred excitation of HShPs in monoclinic β-Ga2 O3 crystals. By virtue of the remarkably enhanced PSHE, our proposed Otto-type multilayer structure shows a superior biosensing performance in which the maximum sensitivity is two orders of magnitude larger than that of previously reported PSHE biosensors based on two-dimensional materials. In addition, the optimized physical and structural parameters including the incident angle, excitation wavelength, azimuth angle and doping concentration of β-Ga2 O3, thickness and refractive index of sensing medium are also investigated and presented. This work unequivocally confirms the strong influence of crystal symmetry on the PSHE, providing important insights into understanding the rich modulation of spin–orbit interactions of light via shear polaritons and therefore facilitating potential applications in photoelectronic devices.